PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN ULANG KONSUMEN PADA PRODUK WARDAH DI KABUPATEN BADUNG - I Gusti Ayu Kadek Yuni Elayanti; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (EMAS, 2022)
The decision to repurchase is created after consumers carry out all the buying processes. In making these decisions, consumers will be influenced by various factors, especially brand image factors, product quality, and price perceptions. The purpose of the study was to analyze brand image, product quality and price perceptions on the decision to repurchase Wardah products in Badung Regency. This research was conducted at one of Wardah's product outlets in Badung Regency. The object of this research is consumers who make repeat purchases at Wardah outlets throughout Badung Regency with specified sample criteria and are related to brand image, product quality, and price perception. The population of this study is all people (consumers) who have purchased Wardah products in Badung Regency with an unknown population. The non-random sampling method in this study used a combination of accidental sampling methods. The number of samples in this study were 150 respondents. Data analysis used multiple linear regression. The result of the research is that brand image has a positive and significant effect on consumer repurchase decisions on Wardah Products in Badung Regency. This is because the brand image (brand image) is closely related to consumer confidence in a brand. Product quality has a positive and significant effect on consumer repurchase decisions on Wardah Products in Badung Regency. Price perception has a positive and significant effect on consumer repurchase decisions on Wardah Products in Badung Regency.